Intermittent structural weakening and acceleration of the Thwaites Glacier Tongue between 2000 and 2018 - B. W. J. Miles; C. R. Stokes; A. Jenkins; J. R. Jordan; S. S. R. Jamieson; G. H. Gudmundsson (Journal of Glaciology, 2020)
Evolving conditions at the terminus of Thwaites Glacier will be important in determining the rate of its future sea-level contribution over the coming decades. Here, we use remote-sensing observations to investigate recent changes (2000–2018) in the structure and velocity of Thwaites Glacier and its floating tongue. We show that the main trunk of Thwaites Glacier has accelerated by 38% over this period, while its previously intact floating tongue has transitioned to a weaker mélange of fractured icebergs bounded by sea ice. However, the rate of structural weakening and acceleration was not uniform across the observational period and we identify two periods of rapid acceleration and structural weakening (2006–2012; 2016–2018), separated by a period of deceleration and re-advance of the structurally-intact shear margin boundary (2012–2015). The timing of these accelerations/decelerations strongly suggests a link to variable ocean forcing. The weakened tongue now has some dependency on landfast sea ice for structural integrity and is vulnerable to changes in landfast ice persistency. Future reductions in landfast sea ice could manifest from changes in climate and/or the imminent removal of the B-22A iceberg from the Thwaites embayment. Such changes could have important implications for the integrity of the ice tongue and future glacier discharge.